Virulence of entomopathogenic hypocrealean fungi infecting Anoplophora glabripennis - Dubois, T.; Hajek, A.; Lund, J.; Bauer, L. (Springer, 2008)
Twenty isolates of four species of entomopathogenic hypocrealean fungi (Beauveria bassiana, Beauveria brongniartii, Isaria farinosa, and Metarhizium anisopliae) were found to be pathogenic to adults of the Asian longhorned beetle, Anoplophora glabripennis. Survival times for 50% of the beetles tested (ST50) ranged from 5.0 (M. anisopliae ARSEF 7234 and B. brongniartii ARSEF 6827) to 24.5 (I. farinosa ARSEF 8411) days. Screening studies initially included strains of B. brongniartii, which is registered as a microbial control agent in Europe, Asia and South America but not in North America. At that time, we could not confirm that this fungal species is native to North America which added uncertainty regarding future registration of this species for pest control in the USA. Therefore, subsequent bioassays documented median survival times for three M. anisopliae isolates (5–6 days to death) and two of these isolates are suggested for further development because they are already registered for pest control in the USA.